Cognitive, Metacognitive, and Personality Manifestations of Gifted Pupils in Solving Word Problems - Jůzová, Kateřina (Scientia in educatione, 2025)
This study focuses on the cognitive, metacognitive and personality manifestations of gifted first graders during word problem solving. A series of meetings with a group of gifted pupils aged 6–7 years (n = 6) were arranged, during which the pupils solved and commented on the solved word problems in a group discussion setting. The problems were selected and pre-tested to ensure clarity and appropriate difficulty. At the same time, they were selected with the aim of containing complicating elements, such as irrelevant information or unknown contexts. The methodology combined problem-solving interviews, group discussions and semi-structured group interviews. In terms of cognitive skills, pupils showed good memory and abstract reasoning skills. Pupils also demonstrated early metacognitive awareness and the ability to use advanced mathematical apparatus. Personality manifestations such as mindset and self efficacy were also observed. Manifestations of fixed and growth mindset and positive and negative self-efficacy were found. The findings suggest that word problems, when used in a structured and reflective environment, can serve as an effective tool for identifying and understanding the thought processes of gifted learners.